Misselection errors in Malay writing among French students - Abdul Halim, Hazlina; Ang, Lay Hoon; Majtanova, Miroslava; Mansor, Nor Shahila (2015)
This study aims to analyse misselection errors made by French students in their learning Malay as a foreign language with regard to the writing skills. The study utilized quantitative and qualitative method of data collection, by applying the definition of misselection errors by Dulay, Burt & Krashen (1982). A total of 10 French respondents participated in this study. The task consisted of the administration of the four writing task by the respondents. The study discovered the most dominant error produced by French students in their Malay written tasks were misselection on lexis (52%), misselection error on affix/ suffix (16%) and misselection errors on the phrases (11%). As a result of this preliminary study, it is hoped that learners can acquire a better understanding of the Malay language; and future study can help classify the errors that learners made and how they could overcome them.